Comparison of performance appraisal system in public and private schools - Hafiz Muhammad Ather Khan; Jawed Hassaan Chandio; Muhammad Tahir Khan Farooqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Performance appraisal is very basic and indispensable for evaluating job performance and setting job standards. In both private and public sector, performance appraisal system exists in some format or in the other. Current study examines current status performance appraisal system and compares the performance of public and private schools. It is found that standards of job performance are different. A 14 item questionnaire was prepared for evaluating job performance; it was piloted upon 40 teachers. Cronbach's alpha value was found as 0.76 which is suitable for administration of research tool on full scale. Sample of the study included 100 Head Teachers. The results of the study show that performance appraisal system in private schools is more effective than that of government schools but classroom environment of government schools is better than private schools.
Keywords: 330; performance appraisal; Bahawalpur; government schools; private schools